Into the storm - Quale, Steven; Armitage, Richard, 1971-; Callies, Sarah Wayne, 1977-; Walsh, Matt, 1964-; Tyler, Brian (Composer) ([Place of publication not identified] : [publisher not identified], 2014)
When a series of strong storms hits a small town, the local residents and a series of storm chasers try to track the storm while documenting the devastation it is causing.
Originally released as a motion picture in 2014.
Dolby digital 5.1, wide screen 1.85:1.
Camera, Brian Pearson ; production design, David R. Sandefur ; editor, Eric Sears ; music, Brian Tyler.
Richard Armitage, Sarah Wayne Callies, Matt Walsh, Max Deacon, Nathan Kress.
MPAA rating: PG-13.
In English, French, or Spanish with optional English, French, or Spanish subtitles.
Keywords: Tornadoes -- Drama; Storms -- Drama; Natural disasters -- Drama; Disaster films; Action and adventure films; Fiction films; Thriller films; Feature films